Determinants Of Muzakki's Level Of Trust Towards The Amil Zakat Institution - Noviana Retnowati; Usnan Usnan (Institut Agama Islam Negeri Padngsidimpuan, 2022)
The purpose of this study was to find out what factors increased muzakki's trust toward the Amil Zakat Institution (LAZ) with a study on LAZ Harapan Umat. The research with a quantitative approach and using a sample of 70 muzakki, found that the level of muzakki trust was influenced by transparency of financial statements, fund management and religiosity, while accountability had no effect on the level of muzakki trust.